Organizational Culture Through The Development Of Management Knowledge, Pedagogical Competence, Work Ethics, Organizational Commitment And Work Motivation - Bagas Koro; Andi Hermawan; Soewarto Hardhienata (Universitas Pakuan, 2023)
The values and norms that are formed and implemented by an organization which must be adhered to by employees and leaders in the organization in order to shape the character of employees in their daily attitudes and behavior in carrying out their respective tasks and functions in order to achieve organizational goals are what is called Culture. Organization. Based on preliminary research, it is known that the organizational culture at PGRI Vocational Schools in Bogor Regency is relatively not optimal. Therefore, research is needed to obtain information on variables related to improving organizational culture. The aim of this research is to carry out strategies and ways to improve organizational culture by conducting research on the influence of the variables Management Knowledge, Pedagogical Competency, Work Ethic, Organizational Commitment and Work Motivation. This research uses the path analysis method to determine the influence between the variables studied and the SITOREM method for indicator analysis to obtain optimal solutions in efforts to improve Organizational Culture.